PREVALENCE OF CRYPTOSPORIDIUM INFECTION AMONG CHILDERN IN KASHAN-IRAN - TALARI, S.A.; MOMTAZMANESH, N.; TALEBILAN, A.; ARBABI, M.; TAGHAVIARDEKANI, A.; TALARI, M.R.; GHASEMZADAE, M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2002)
Cryptosporidiosis is one of the pathogenic parasites of human with different prevalence in each region of the world including our country. This is a self limited parasitic infection which may produce sever fatal disease in immunodeficient patients. Due to lack of information about the rate of human infections by this parasite in Kashan, this study was conducted to determine the rate of infection by the mentioned parasite in the childern with diarrhoea referred to central laboratory of Kashan, Iran during 2000-2002. A cross sectional descriptive study was performed on 240 stool samples taken by random sampling from childern suffering from intestinal discomforts. Formalin-ether concentration of fecal samples and warm Ziehl-Neelsen stain method was used and the smears were studied under light microscope. The highest rate of prevalence was found in rural areas and childern over 5-yrs of age. The prevalence of infection in the hot seasons (ie spring and summer) of the year was also more than the cold seasons (i.e. autum and winter). It was also observed the prevalence of infection in those people who were in contact with cattles was more than others. Keeping in view the 3.75% prevalence of cryptosporidium infection among childern under research, it is hereby recommended that the diagnostic centres pay more attention to this parasite particularly in those cases of diarrhoea where no other pathogenic agent is found in stool.